GENETIC DIVERSITY ASSESSMENT IN LENTIL (LENS CULINARIS MEDIKUS) GENOTYPES THROUGH ISSR MARKER - JOSHI, MEENAKSHI; S. K. VERMA,; J. P. SINGH,; BARH, ANUPAM (The Bioscan, 2013)
The genetic diversity study was conducted in 24 lentil genotypes at Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhand, India. In the present investigation 20 ISSR (Inter Simple Sequence Repeat) primers were taken, out of these only seven primers gave amplification. These primers gave a total of 44 loci, out of which 36 were polymorphic. ISSR primers 8161-054 at 500 bp, 8161-055 at 700bp and 8161-058 at 1200 bp gave unique bands for different genotypes clearly indicating that these three primers can be used to identify different lentil genotypes. Genetic distances were calculated using Jaccard’s Similarity Coefficient, displayed in a dendrogram (UPGMA method). Dendrogram generated by cluster analysis derived from ISSR markers divided 24 lentil genotypes into two clusters A and B at 41% similarity. Major cluster A comprised of 23 and B of one genotype. On the basis of Jaccard’s similarity coefficient genotypes PL-098 and L-4147 (0.41) were found genetically most distant suggesting that these varieties can be used in future hybridization programmes to generate desirable segregants. The study Indicates ISSR as a useful tool in determining the genetic diversity among genotypes in lentil as it is not influenced by environmental conditions.